THE EFFECTIVENESS OF PROJECT-BASED LEARNING ON ELEMENTARY SCHOOL STUDENTS’ CREATIVITY - Azizi, Muhammad Alfi; Mendes, Clara; Silva, Pedro (International Journal of Educatio Elementaria and Psychologia, 2025)
Fostering creativity is a critical objective of 21st-century education, yet traditional pedagogical approaches often fall short of developing this essential skill. Project-Based Learning (PjBL) has been proposed as a student-centered model that can enhance creative thinking by engaging students in authentic, complex tasks. This study aimed to quantitatively determine the effectiveness of the PjBL model on the creativity of elementary school students. A quasi-experimental research design was employed, utilizing a pre-test/post-test non-equivalent control group. The sample consisted of two fourth-grade classes, one serving as the experimental group receiving the PjBL intervention and the other as a control group receiving conventional instruction. Student creativity was measured using a validated instrument assessing fluency, flexibility, originality, and elaboration. The collected data were analyzed using an independent samples t-test. The results revealed a statistically significant difference between the post-test scores of the two groups (p < 0.05), with the experimental group demonstrating a substantially higher average creativity score. The analysis indicated that the PjBL model was significantly more effective in enhancing students’ creative thinking skills compared to traditional teaching methods. This study concludes that PjBL is a highly effective pedagogical strategy for fostering creativity in elementary education and recommends its broader implementation to better prepare students with the skills needed for future challenges.